The phosphorus load and the variation of the trophic states of Cirata Reservoir (West Java, Indonesia) from 1988 to 2017 - Niken Pratiwi; ZULHAMSYAH IMRAN; INNA PUSPA AYU; ALIATI ISWANTARI; DWI YUNI WULANDARI (Society for Indonesian Biodiversity, 2020)
Abstract. Pratiwi NTM, Imran Z, Ayu IP, Iswantari A, Wulandari DY. 2020. The phosphorus load and the variation of the trophic states of Cirata Reservoir (West Java, Indonesia) from 1988 to 2017. Biodiversitas 21: 4176-4183. Cirata Reservoir was constructed in 1987 between Saguling and Jatiluhur Reservoirs; these are the three man-made cascading lakes in West Java, Indonesia. Cirata Reservoir has been used for floating cage aquaculture activities. The high organic content from the remains of the fish pellets raised the phosphorus (P) load, resulting in the eutrophication of the reservoirs. This research was aimed to assess the P load and the variation of the trophic states of the reservoir from year 1988 to 2017. The trophic states and the nutrients’ conditions of the water were determined using Myxophycean Index. Four groups of phytoplankton were found in the reservoir during observation: Cyanophyceae, Chlorophyceae, Bacillariophyceae, and Dinophyceae. In addition, one group was found in a smaller number of observations: Eugolenophyceae. Although the community structure of the phytoplankton has changed, the Cyanophyceae was always dominant in response against the condition of nutrients, especially P. The P load is closely related to the number of floating cages in the reservoir. This evidence showed that Cirata Reservoir tended to be relatively eutrophic. In general, despite that the P load tended to fluctuate, the trophic states of Cirata Reservoir remained dynamic in relatively high conditions; showed by the oligo-mesotrophic state during its first year of operation, then increased to eutrophic and hypertrophic by the next decade. Although the P load tended to decrease, it remains in the eutrophic condition in the recent time.